Thalamic GABA levels and Occupational Manganese Neurotoxicity: Association with Exposure Levels and Brain MRI - Ma, Ruoyun E. (Neurotoxicology, 2017)
Excessive occupational exposure to Manganese (Mn) has been associated with clinical symptoms resembling idiopathic Parkinson’s disease (IPD), impairing cognitive and motor functions. Several studies point towards an involvement of the brain neurotransmitter system in Mn intoxication, which is hypothesized to be disturbed prior to onset of symptoms. Edited Magnetic Resonance Spectroscopy (MRS) offers the unique possibility to measure γ-amminobutyric acid (GABA) and other neurometabolites in vivo non-invasively in workers exposed to Mn. In addition, the property of Mn as Magnetic Resonance Imaging (MRI) contrast agent may be used to study Mn deposition in the human brain. In this study, using MRI, MRS, personal air sampling at the working place, work history questionnaires, and neurological assessment (UPDRS-III), the effects of chronic Mn exposure on the thalamic GABAergic system was studied in a group of welders (N=39) with exposure to Mn fumes in a typical occupational setting. Two subgroups of welders with different exposure levels (Low: N = 26; mean air Mn = 0.13±0.1 mg/m(3); High: N = 13; mean air Mn = 0.23±0.18 mg/m(3)), as well as unexposed control workers (N = 22, mean air Mn = 0.002±0.001 mg/m(3)) were recruited. The group of welders with higher exposure showed a significant increase of thalamic GABA levels by 45% (p<0.01, F(1,33) = 9.55), as well as significantly worse performance in general motor function (p < 0.01, F(1,33) = 11.35). However, welders with lower exposure did not differ from the controls in GABA levels or motor performance. Further, in welders the thalamic GABA levels were best predicted by past-12-months exposure levels and were influenced by the Mn deposition in the substantia nigra and globus pallidus. Importantly, both thalamic GABA levels and motor function displayed a non-linear pattern of response to Mn exposure, suggesting a threshold effect.